The transition from collegiate sport: An analysis of the current retirement planning practices of NCAA institutions. Issue 1 (2nd January 2023) - Kiefer, Heather R.; Petrie, Trent A.; Walls, Ray
ABSTRACT: The NCAA provides limited guidelines to member institutions regarding preparing student-athletes for retirement from sport, and as a result, different schools are developing their own programs. This study explored what NCAA athletic departments do to prepare their student-athletes for their graduation and transition out of sport. Participants were athletic department personnel, and they completed a survey that assessed for current retirement planning practices and available campus resources for student-athletes who are transitioning out of sport. Frequencies, t -tests, and chi-square analyses were used to assess trends across Divisional Levels. Analyses show that significantly more DI than DII/DDIII institutions have retirement planning programs and there is no significant difference between the topics that are covered. The degree to which participants agreed that athletic departments have an ethical/moral responsibility and their perception of responsibility of preparing student-athletes varied significantly across Divisional Level. Implications of the findings, limitations, and future directions are discussed.